Design and Fabrication of High-Performance Piezoelectric Micromachined Ultrasonic Transducers Based on Aluminum Nitride Thin Films - Le Zhang; Kunxian Yan; Lei Ye; Xiangyu Luo; Jian He; Xiujian Chou (Micromachines, 2024)
Ultrasound is widely applied in diverse domains, such as medical imaging, non-destructive evaluation, and acoustic communication. Piezoelectric micromachined ultrasonic transducers (PMUTs) capable of generating and receiving ultrasonic signals at the micrometer level have become a prominent technology in the field of ultrasound. It is important to enrich the models of the PMUTs to meet the varied applications. In this study, a series of PMUT devices featured with various top electrode configurations, square, circular, and doughnut, were designed to assess the influence of shape on the emission efficacy. It was demonstrated that the PMUTs with a circular top electrode were outperformed, which was calculated from the external acoustic pressure produced by the PMUTs operating in the fundamental resonant mode at a specified distance. Furthermore, the superior performance of PMUT arrays were exhibited through computational simulations for the circular top electrode geometries. Conventional microelectromechanical systems (MEMS) techniques were used to fabricate an array of PMUTs based on aluminum nitride (AlN) films. These findings make great contributions for enhancing the signal transmission sensitivity and bandwidth of PMUTs, which have significant potential in non-destructive testing and medical imaging applications.